Assessment of the Relationship among e-Service Quality Dimensions, Customer Satisfaction, and Loyalty- Survey Evidence - Goel , Pooja (Gyan Management Journal, 2017)
Loyal customers are on the wish list of every company but to get the loyalty glue is not an easy task for any firm especially when the buyers in this information age any time can compare the products, level of services, prices, delivery promises etc. Competitive market place has made consumer more and more demanding. Clearly in e-commerce setting, all companies need to consider and evaluate e-marketing opportunities thoroughly. Within the light of these evaluations this study aims to assess effect of the dimensions of online service quality on loyalty and the mediating role of customer satisfaction on service quality dimensions and loyalty. The survey target sample consisted young population i.e. up to the age of35 years living in National Capital Region (NCR), who had successfully completed at least one online transaction recently from any online retailer. The instrument used for the study consists of three dimensions to evaluate online service quality. The scale used is based on the previous studies. The convenience cum snowball sampling has been used for the study. The resulting sample comprised of 155 valid questionnaires, which were considered suitable for the study. Results of the study show that reliability and privacy has significant direct relationship with loyalty and function and reliability has reported strong relationship with satisfaction. Our results also confirm that satisfaction is one very important factor antecedentof loyalty. However, partial mediation of satisfaction has been reported by the survey results on the relationships of dimensions of service quality and loyalty.